Improving loan repayment in Ghana: Does financial literacy matter? - Samuel Tawiah Baidoo; Hadrat Yusif; Enock Kojo Ayesu (Cogent Economics & Finance, 2020)
Loan defaults continue to be a major challenge that confronts financial institutions in developing countries and this impedes their potential role in sustainable development. Given the enormity of loan defaults, policymakers have devoted much attention to the phenomenon by implementing strategies and policies aimed at improving loan repayment to avert the situation. To complement the effort of policymakers, several empirical studies have also been conducted regarding loan repayment determinants; but what is worrying is that none of these studies emphasises the role of financial literacy, especially in the Ghanaian context. This study therefore examines the potential effect of financial literacy on loan repayment. We rely on primary data and employ the binary probit regression for the analysis. The results reveal a positive and significant relationship between financial literacy and loan repayment. This means that enhancing financial literacy improves loan repayment significantly which will in turn ensure sustainability of the financial institutions. The level of education of borrowers is also revealed to play a key role in loan repayment. Given the findings, the study sheds new lights on how loan repayment can be improved to ensure a vibrant banking sector.
Keywords: C25; D14; G20; G21; 330; financial institutions; financial literacy; Ghana; loan default; loan repayment